ความสัมพันธ์ระหว่างความสามารถด้านการบริหารของหัวหน้าหอผู้ป่วย การทำงานเป็นทีมของทีมสุขภาพกับประสิทธิผลของหอผู้ป่วย ตามการรับรู้ของพยาบาลประจำการโรงพยาบาลทั่วไป สังกัดกระทรวงสาธารณสุข - สมสมร เรืองวรบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
To study the relationships between head nurses administrative abilities, teamwork of healthcare team, and effectiveness of patient units as perceived by staff nurses, and to determine variables which could be predicted effectiveness of patient units as perceived by staff nurses, general hospitals under the jurisdiction of the Ministry of Public Health. The research subjects consisted of 399 staff nurses, randomly selected by stratified random sampling technique. The research instruments were adopted and developed by the researcher, namely head nurses administrative abilities, teamwork of healthcare team, and effectiveness of patient units questionnaires. The instruments Cronbach s alpha coefficients were .96, .91 and .86 respectively. The data were analyzed by Pearson s product moment correlation coefficients and multiple regression analysis. The major findings were as followed 1. There was positively significant relationship between head nurses administrative abilities and effectiveness of patient units as perceived by staff nurses (r=.38) at .01 level. 2. There was positively significant relationship between teamwork of healthcare team and effectiveness of patient units as perceived by staff nurses (r=.38) at .01 level. 3. Variables that could predicted effectiveness of patient units as perceived by staff nurses were teamwork of healthcare team, and head nurses administrative abilities at .01 level. The predictors accounted for 31.7% of variance (R2=0.317). The predictors equation in standard scores form can be stated as followed: Z =0.462* teamwork of healthcare team+0.183* head nurses administrative abilities